Education of Honesty and Sincerity in The Qur'an as Part of Humanity - Asrizal Saiin; Candra Wesnedi; Zaitun Zaitun; Muh. Rizki (Al-Riwayah : Jurnal Kependidikan, 2022)
The Qur'an regulates how to portray human qualities as desired by Allah. The purpose of this research is to study and recognize the nature of humanity in the form of honesty and sincerity based on the Qur’an, so that it can convince humans that honesty and sincerity are important and must exist in humans. The method used in this paper is a qualitative method with a literature review. This research is descriptive-analytical. The data that has been collected is then analyzed by the deductive method. From this research, it is known that honest and sincere nature is an important trait and must be possessed by a human being. Al-Qur'an very much describes the nature of honesty and sincerity. The verses of the Qur'an that explain the nature of honesty and sincerity are found in Surah Maryam (19): 50; as-Syu'ara (26): 84; an-Nisa (4): 125; al-Baqarah (2): 125; as-Shaffat (37): 102-107; at-Taubah (9): 119; an-Nahl (16): 105; al-Ahzab (33): 24; Muhammad (47): 31; Ali 'Imran (3): 179; ash-Shaff (61): 2-3; QS at-Taghabun (64): 16.